The tumour stromal features are associated with resistance to 5‐FU‐based chemoradiotherapy and a poor prognosis in patients with oral squamous cell carcinoma. Issue 3 (31st December 2014) - Matsuoka, Yuichiro; Yoshida, Ryoji; Nakayama, Hideki; Nagata, Masashi; Hirosue, Akiyuki; Tanaka, Takuya; Kawahara, Kenta; Nakagawa, Yoshihiro; Sakata, Jyunki; Arita, Hidetaka; Hiraki, Akimitsu; Shinohara, Masanori
<x xml:space="preserve">Abstract</x> It has been increasingly recognized that the tumour microenvironment is a critical factor involved in cancer progression. However, little is known about the clinical value of the stromal features in oral squamous cell carcinoma (OSCC). The purpose of this study was to determine the clinical significance of cancer‐associated fibroblasts (CAFs) and tumour‐associated macrophages (TAMs) in OSCC. OSCC specimens were obtained from 60 patients who underwent surgery following 5‐fluorouracil‐based chemoradiotherapy. Paraffin‐embedded sections obtained from biopsy specimens were immunohistochemically analysed. The associations among CAFs, TAMs and various clinicopathological features were examined, and the effects of CAFs and TAMs on the prognosis were evaluated. In the group with a high level of CAFs, the incidence of advanced pT‐ and pN‐stage cases was significantly higher than that in the group with the low level. A high TAMs tumour expression was significantly correlated with a poor response to preoperative chemoradiotherapy. A Kaplan–Meier analysis revealed that higher numbers of CAFs and TAMs were significantly correlated with a poor prognosis. These findings suggest that TAMs are a potential biomarker for predicting the clinical response to 5‐FU‐based chemoradiotherapy, and the expression status of the CAFs and TAMs may be useful for making treatment decisions to improve the survival of OSCC patients.